Why did Swiss citizens refuse to ban tobacco advertising?. Issue 2 (1996) - Cornuz, J; Burnand, B; Kawachi, I; Gutzwiller, F; Paccaud, F
Abstract : A ban on tobacco advertising is one of the major tools to promote tobacco control. Swiss citizens recently refused to modify the Swiss Constitution to ban tobacco advertising. This case study shows how a strong alliance among the tobacco industry, the state, the media, and sports and cultural activities planners made it difficult for people to make an informed decision. The promoters of the ban were unable to provide counter-arguments to the mostly fallacious claims made by the opponents regarding the likely health and economic impact of this ban. A comparison to successful campaigns in Canada and New Zealand provides insight regarding factors missing in the Swiss campaign which might have been useful in obtaining support from Swiss citizens.